Treffinger Model on Student Learning Outcomes in Grade IV Science Learning at Elementary School - Eni Marta; Elvina Elvina; Rinja Efendi; Rejeki Rejeki; Abdul Putra Ginda; Sari Angreani (Jurnal Penelitian Pendidikan IPA, 2024)
While conducting observations at SD Negeri 022 Rambah, the researcher encountered several problems faced by students and teachers at SD Negeri 022 Rambah during the learning process, the problems encountered were as follows; The science learning process that takes place at school is still not enjoyable, Teachers only use the lecture method, and Low student learning outcomes occur at SD Negeri 022 Rambah among class IV students. The treffinger learning model is a learning model that leads to critical and creative thinking skills. This research is Classroom Action Research. Data collection techniques in this research used observation sheets and tests. Data analysis techniques by analyzing data from observation sheets and tests carried out by students. The research results show an increase in learning outcomes with the application of the Treffinger learning model. In cycle 1, meeting 1, the number of students who completed 8 students became 11 students with an average score of 76.30 with a student learning completion percentage of 55%. Experiencing an increase in cycle 2, the number of students who completed 13 students at meeting 1 became 17 students with a completion percentage of 85% with an average class score of 83. It can be concluded that the application of the treffinger learning model can improve student learning outcomes at SD Negeri 022 Rambah Samo.